Optimalisasi Limbah Batang Pisang Kepok untuk Pemberdayaan Perempuan dan Peningkatan Kesejahteraan Masyarakat di Desa Tadenas, Pulau Moti, Maluku Utara - Mila Fatmawati; Nursamsi Nursamsi; Hamidin Rasulu; Nurjanna Albaar; Herman Darwis (Jurnal Pertanian Khairun, 2025)
The utilization of kepok banana stem waste is still not optimal in Tadenas Village, Moti Island, North Maluku. So far, banana stems are only considered as worthless agricultural leftovers. The main problem faced by the community, especially women, is the limited knowledge in processing local waste into innovative products that can be marketed. This activity aims to empower women through optimizing kepok banana stem waste into innovative jerky products with the "Mila Rasa" brand, as well as encouraging the improvement of community welfare through local potential-based businesses. The implementation method uses a participatory approach with stages: (1) identification of the potential of local raw materials, (2) socialization and counseling regarding the nutritional value and business opportunities of products, (3) production assistance and quality standardization on processing banana stems into jerky, and (4) introduction of simple marketing strategies. The results of the study showed a significant increase.